2021
DOI: 10.1021/acsami.1c17420
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Targeted Nanoplatform Regulating the Bone Immune Microenvironment Enhances Fracture Healing

Abstract: The immune system and skeletal system are closely linked. Macrophages are one of the most important immune cells for bone remodeling, playing a prohealing role mainly through M2 phenotype polarization. Baicalein (5,6,7-trihydroxyflavone, BCL) has been well documented to have a noticeable promotion effect on M2 macrophage polarization. However, due to the limitations in targeted delivery to macrophages and the toxic effect on other organs, BCL has rarely been used in the treatment of bone fractures. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 59 publications
0
25
0
Order By: Relevance
“…It is widely believed that different macrophage polarization states contribute to different conditions of bone metabolism [ 3 , 21 , 22 ]. Zhou et al demonstrated that induction of M2 polarization facilitated osteogenic differentiation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is widely believed that different macrophage polarization states contribute to different conditions of bone metabolism [ 3 , 21 , 22 ]. Zhou et al demonstrated that induction of M2 polarization facilitated osteogenic differentiation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely believed that different macrophage polarization states contribute to different conditions of bone metabolism [ 3 , 21 , 22 ]. Zhou et al demonstrated that induction of M2 polarization facilitated osteogenic differentiation [ 21 ]. Kang et al demonstrated that the M2 macrophage extracellular vesicles increased osteoinductive gene expression of MSCs [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory microenvironment mediated by the immune system in vivo is considered to be a major reason of abnormal bone metabolism. It may lead to osteoclast activation to accelerate bone loss [27,28], increase the risk of fracture [29,30], and slow down the healing rate of fracture [31,32]. Many medicines are used to treat osteoporosis and repair the bone tissue by alleviating the expression of tissue inflammatory factors [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of MSN–SS–alkyne is referred to in our previous work. ,, 100 mg of MSN–SS–alkyne was dispersed in a mixed solution of 5 mL of methanol and 5 mL of PBS. 25 mg of DOX hydrochloride or 25 mg of RRx-001 was added, and the reaction mixture was vigorously stirred at room temperature for 24 h. Then, 100 mg of mono-6-azido-β-CD, 100 mg of CuSO 4 ·5H 2 O, and 170 mg of sodium ascorbate were added.…”
Section: Methodsmentioning
confidence: 99%